PENGELOLAAN PEMBELAJARAN BAHASA INGGRIS BERBASIS COOPERATIVE AND INOVATIVE (Studi Situs SMK Muhammadiyah 1 Prambanan Klaten) - Suyoto, Suyoto (2011)
Research purposes to (1) describe learning interaction character between teacher and students in cooperative and innovative English learning based in SMK Muhammadiyah 1 Prambanan Klaten. (2) describe media using in cooperative and innovative English learning based in SMK Muhammadiyah 1 Prambanan Klaten. (3) describe students learning activity character in class in cooperative and innovative English learning based in SMK Muhammadiyah 1 Prambanan Klaten. This is a qualitative research. Research conducted in SMK Muhammadiyah 1 Prambanan Klaten. Collecting data technique are observation, depth interview, and documentation method. Analysis in qualitative structural site research includes three main components they are data reduction, data presentation and conclusion with verification. This research results are (1) Teacher and students interaction in cooperative and innovative English learning based by teacher purposes to help students in improving knowledge, attitute and English ability, each teacher and students realize the important of learning purposes. Teacher and students interaction in planning learning, designed to reach the goal with procedures and relevant sistematic steps to place students as centre and they have purposes. (2) Media using in cooperative and innovative English learning based, done by teacher with planning of media will be used in learning, how to use it and how to keep it. Learning media planning is one which have to planned by teacher in lesson plan (RPP) media learning using planning in RPP. All learning media planned including multimedia learning media and as one of some exist medias. Multimedia learning media using based on student interest. (3) Student preparation before learning process are bringing and preparing English learning equipment by making student coordination. Classroom preparation before learning is ready to be used everyday. Students on duty come earlier to prepare it. Basicly cooperative and innovative English learning points on student learning experience form (learning cooperative).